Clinical features and genetic analysis of a family with t(5;9) (p15;p24) balanced translocation leading to Cri-du-chat syndrome in offspring - Zhao, Jing; Chen, Ping; Ren, Yijia; Li, Shurong; Zhang, Weiyi; Li, Yan; Wang, Fengyu (Frontiers in Genetics, 2025)
BackgroundBalanced translocations are common chromosomal structural abnormalities that usually do not involve a gain or loss of genetic material; and carriers usually display normal phenotypes and intelligence. However, unbalanced rearranged gametes can be produced during the meiotic division of reproductive cells, leading to infertility, miscarriage, stillbirth, or the birth of newborns with malformations and chromosomal abnormalities. These adverse pregnancy outcomes create significant burdens for families and societies and affect the quality of life of newborns, threatening their health.ObjectiveIndividuals carrying balanced translocations can have phenotypically normal offspring, but they also face high risks of natural miscarriage and giving birth to newborns with chromosomal abnormalities. We characterized individual clinical features and conducted a genetic analysis of the members of a family with t (5; 9) (p15; p24) balanced translocation leading to Cri-du-chat syndrome in the offspring.Study designWe performed a chromosomal karyotyping with high-resolution G-banding on the proband and her family members to detect their chromosomal configurations. We also used chromosomal microarray analyses (CMA) to detect copy number variants. Enrichment analysis of genes in the duplicated or deleted regions of 5p and 9p was performed using Metascape. Results: The proband (III7), her father (II3), her brother (III5), and her cousin (III14) were all carriers of the t (5; 9) (p15; p24) balanced translocation. Offspring (IV5, IV7, IV9, and IV12) were affected. Genetic microarray results of IV7 showed a 26.3 Mb deletion on chromosome five and a 15.3 Mb duplication on chromosome 9. Genetic microarray results of IV5, IV9, and IV12 showed a 26.5 Mb duplication on chromosome five and a 15.4 Mb deletion on chromosome 9.ConclusionThis study reports a rare familial balanced translocation pedigree, particularly noting that the offspring can suffer from Cri-du-chat syndrome, which suggests a potential new genetic model for this syndrome. It provides novel insights for genetic counseling and prenatal diagnosis in patients with adverse pregnancy outcomes before attempting another pregnancy.